(3aUhd CHbQGWs - (3GHbQGW GdMcjes ((3GdehUd s)
(3ChdgG (B:s
(3GdebGdI GdChdi aj JOHjQ GdCeQGV hJOHjQ GdeQVi hYOO aUhdgG , GdYeQ bUjQ , hGdUfGYI WhjdI , hGdhbJ Vfjf hGdJLQHI NWQ, hGdbVGA YSQ s
(3BNQgG (B:s
(3NQhL GdHOf Yf WHjYJg, ceG jNQL ajeG jSJaQZ ef GdeKGfI , hajeG jSJaQZ ef GddMe Ch ef ZjQg ef GdHOf Chef ZjQg cGf Pdc OdjdkG Ydi GdehJ s
(3fSNI KGfjIs
(3eYgG ChUGa CHbQGW aj GdHKhQs
(3hbO GNJdWJ ChQGbgG CKfGA GdJLdjOs
(3ocJHJ GdfSNI HJQHI GdMGL fLe GdOjf YfHQ Gdefhfj GdShbGQj Ydi TGWF OLdIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
Keywords: (3GdWHs